2008
DOI: 10.1111/j.1440-6055.2008.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and diversity of termites in a savanna woodland reserve in tropical Australia

Abstract: This study contributes to the paucity of knowledge on the structure of Australian tropical savanna termite assemblages, compared with that available for tropical savannas elsewhere in the world. Termite species diversity, frequency of occurrence and functional diversity in Charles Darwin National Park, a savanna woodland reserve in tropical northern Australia, were assessed. In four 50 ¥ 50 m sites, a direct search and bait sampling protocol was used to sample mounds, standing and lying dead wood, litter, soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…For total site exchange, it has to be noted that termite mounds have been identified as hotspots of N 2 O emissions in savannas (e.g., Brümmer et al, 2009b) and are abundant in savannas of tropical Australia (Dawes-Gromadzki, 2008), but the total contribution to the soil-atmosphere exchange is highly variable in space. It was also reported that belowground termite activity can (often only temporarily) add to on-site variability of measured in situ fluxes (Livesley et al, 2011).…”
Section: N 2 O Emissionsmentioning
confidence: 99%
“…For total site exchange, it has to be noted that termite mounds have been identified as hotspots of N 2 O emissions in savannas (e.g., Brümmer et al, 2009b) and are abundant in savannas of tropical Australia (Dawes-Gromadzki, 2008), but the total contribution to the soil-atmosphere exchange is highly variable in space. It was also reported that belowground termite activity can (often only temporarily) add to on-site variability of measured in situ fluxes (Livesley et al, 2011).…”
Section: N 2 O Emissionsmentioning
confidence: 99%
“…Active searching transects, on the other hand, sample all termites, but are labour intensive and often less effective for hard savanna soils (although see e.g. , Dawes-Gromadzki 2005, 2008.…”
Section: Termites (Blattodea: Termitidoidae) Are Important Ecosystem mentioning
confidence: 99%
“…Once the species are deprived of sufficient amounts of litter or when the density of termite mounds is high, they resort to standing biomass and can consume more than 60% of the standing crop. In the current study, specialized grass feeders such as Trinervitermes oeconomus were very rare and this could be attributed to the low plant richness of the ground layer and the general patchiness of ground vegetation (Dawes-Gromadzki, 2008). Further, the deterioration of rangeland ecosystem attributable to overgrazing and indiscriminate tree cutting could have derived members of the sub-family Macrotermitinae of adequate litter for nourishment which in turn resorted to grass for survival.…”
Section: Composition Of Termite Speciesmentioning
confidence: 98%
“…Epigeal-nesting species were the most common species followed by hypogeal-nesting species and this was attributed to the high termite encounter rates in mounds and lying dead wood. Dawes-Gromadzki (2008) also noted that epigeal nesting species were the most abundant species accounting for 88% of the total species in Savanna woodland reserve in Tropical Australia. Wood-nesting species were also represented but arboreal-nesting species were very rare.…”
Section: Composition Of Termite Speciesmentioning
confidence: 99%
See 1 more Smart Citation